MORAL HAZARD DAN AGENCY COST (Pencederaan Kontrak Bisnis dalam Perspektif Ekonomi Syarî’ah) - wadhan wadhan (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2008)
A contract for business organization or production process may generally involve Principal- agent problems due to information asymetry. Islâmic business contracts has manifold avenues and modalities to be implemented as according to the suitability of time, place and environment.The essential benefits of the Islâmic business contracts is to ensure the benefit of the both partners in the contract. Since the contract for business organization or production process embodies some sort of problems like principal- agent problem due to information asymetry and moral hazard, this also be easily minimised in an Islâmic contract. Therefore, it may be said that if in an Islâmic economy, Islâmic firm implements the business contract as designed and approved by the shariah, then principal- agent problem will be minimised and society will be more benefited from the welfare motive of the producer and other market agents.